2012
DOI: 10.1186/1758-3284-4-30
|View full text |Cite|
|
Sign up to set email alerts
|

Solitary giant neurofibroma of the neck subjected to photodynamic therapy: case study

Abstract: Photodynamic therapy (PDT) - the fourth modality - has been successfully used in the management of early and advanced pathologies of the head and neck. We studied the effect of this modality on a giant solitary neurofibroma of the neck. A 70-year-old Caucasian female presented with left neck pain and disfigurement associated with slight shortness of breath and dysphagia. Examination revealed a large mass in the neck with no neurovascular compromise. Magnetic resonance imaging (MRI) reported a heterogeneously e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Neurofibroma is an uncommon benign neoplasm which originates from nerves that is composed of Schwann cells, perineural cells and fibroblasts. Soft palatal neurofibromas are rare and present with slowly growing painless mass [2]. Generally, neurofibromas present as either solitary mass or as part of neurofibromatosis syndrome or von Recklinghausen’s disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibroma is an uncommon benign neoplasm which originates from nerves that is composed of Schwann cells, perineural cells and fibroblasts. Soft palatal neurofibromas are rare and present with slowly growing painless mass [2]. Generally, neurofibromas present as either solitary mass or as part of neurofibromatosis syndrome or von Recklinghausen’s disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…Neuro broma is a rare benign nerve sheath tumor composed of Schwann cells, perineural like cells and broblasts (10). It can be found in any peripheral nerve that can be invaded by neuro broma, especially in lower limbs and upper limbs (2).…”
Section: Discussionmentioning
confidence: 99%
“…But biopsy has a risk of causing nerve damage, which is likely to occur in this case as intraoperatively, we found that some of the nerve ber tracts were extruded particularly thinly by the tumor. At present, the rst choice of clinical treatment for neuro bromas is still complete resection, especially when symptoms occur or appearance are affected, the postoperative prognosis is good and the recurrence rate is low (2,10). However, the parent nerve of neuro bromas is usually unseparable in solitary neuro bromas (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofibroma is a benign nerve sheath tumour in the peripheral nervous system, constituting about 5% of all the benign soft-tissue neoplasms in the body originating from the Schwann cells or the perineural fibroblast cells 1. Patents in the third decade of life are mostly affected by the disease and there is no significant sex predilection between the males and the females 2.…”
Section: Introductionmentioning
confidence: 99%